STUDY ON APPLICATION OF GEOGRAPHICAL INFORMATION SYSTEM (GIS) FOR ESTABLISHMENT OF BIOMASS CLASSIFICATION TO SUPPORT IMPLEMENTATION OF CLEAN DEVELOPMENT MECHANISM - Gun Mardiatmoko; Th.M. Silaya; Jan W. Hatulesila (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2012)
A research to study biomass classification by using GIS has been conducted at forest area in Ambon, Province of Maluku. The aims of this research were to find out composition of forest vegetation with its distribution, to determine biomass potency distribution of vegetation and to make classification of biomass potency, air temperature and light intensity distribution. This research used survey method. The vegetation biomass was measured by using allometric and weighted scoring method. By using GIS, definite score can be formatted. The result showed that composition of forest vegetation could be determined, and its biomass potency could be measured and presented on digital map. The digital map of biomass potency, air temperatures and light intensity distribution can be arranged successfully with 3 classifications: low 0.15 ha (17%), moderate 0.31 ha (37%) and high 0.39 ha (46%). Keywords: biomass classification, LULUCF, CDM, GIS, allometric equation